Fabrication and performance of the wide-band highly shielded polyvinylidene fluoride film - Fu, Liwu; Hu, Jiangfeng; Luo, Peng; Xiang, Dong; Hui, Wenying; Cheng, Lei; Zhou, Yan; Zhengrong, Xiong; Yao, Dengzun; Jing, Xianghai (Frontiers in Materials, 2025)
The white weathering layer materials that can effectively block the entire solar light band is of great importance for improving the service life, safety, and reliability of the materials. In this work, CsxWO3@PDA was prepared by in situ polymerization to achieve high absorption in the full spectral range and increase the compatibility between CsxWO3 particles and polyvinylidene fluoride (PVDF). PVDF composite films with different particle contents were prepared through compounding with titanium dioxide (TiO2) and CsxWO3@PDA. The prepared composite films were characterized by FT-IR, field emission scanning electron microscopy, universal material testing machine, whiteness meter, and ultraviolet visible spectroscopy. The results showed that the CsPVDF composite films with CsxWO3@PDA and TiO2 exhibited a whiteness level higher than 74, a transmittance of less than 5% in the wavelength range of 200–2500 nm, and a transmittance close to zero in the range below 1750 nm, demonstrating excellent shielding effect. The xenon lamp aging test also confirmed that the composite films had excellent weather resistance after aging 500 h. At the same time, adding a certain amount of CsxWO3@PDA could improve the tensile strength of PVDF.